Tindak Pidana Korupsi di Masa Pandemi Covid-19 dan Dampaknya Terhadap Pemenuhan Hak Asasi Manusia: Corruption in the Covid-19 Pandemic Period and Its Impact on the Fulfillment of Human Rights - Arifin, Ridwan; Syariefudin, Iqbal; Holish, Amarru Muftie (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Corruption is a complex problem for the Indonesian nation and state, not only a matter of law enforcement, but the impacts of this crime are widespread and affect almost all sectors from the lowest to the highest levels. Many studies related to criminal acts of corruption only focus on the punishment of perpetrators and the patterns of formation and development of these crimes in society. Research related to the impact of corruption is only limited to research on the amount of state losses and economic financial calculations, only a few have examined the socio-economic impact of corruption. When the criminal act of corruption is confronted with human rights, research studies that arise relate to the rights of the perpetrators of corruption in the framework of protecting human rights. In fact, corruption has a broad dimension and has a significant impact on the fulfillment of human rights in all sectors.